Beclin-1 and LC3B expression in canine mast cell tumours: an immuno-ultrastructural and immunohistochemical study of autophagy - Giovanna P. Vicente; Leonardo Della Salda; Ricardo F. Strefezzi (Veterinary Quarterly)
Mast cell tumours (MCTs) are common malignant neoplasms in dogs, for which prognosis and therapeutic decisions are based on histological features and proliferation markers. Autophagy is a cellular catabolic process responsible for degrading cytoplasmic components to maintain homeostasis, alterations in which are frequently linked to tumour growth and progression. This study was conducted to investigate the occurrence of autophagy in canine MCTs and to verify its value as a prognostic indicator for dogs with the disease. Beclin-1 and LC3B expressions were investigated using immunohistochemistry, and autophagy was ultrastructurally characterised. The autophagic phenomenon was successfully visualised in neoplastic mast cells under transmission electron and immunoelectron microscopy. MCTs from dogs that died due to the disease showed higher positivity for Beclin-1 and dogs with MCTs presenting a LC3B granular immunohistochemical pattern had a significantly shorter post-surgical survival. The occurrence of autophagy is an indicator of poor prognosis. Future studies are needed to elucidate the specific mechanisms and open new opportunities to treatments targeting this cancer cell advantage.